Integrating nowcasting with crisis management and risk prevention in a transnational and interdisciplinary framework - Yong Wang; Ingo Meirold-Mautner; Alexander Kann; Alenka Šajn Slak; André Simon; Jozef Vivoda; Benedikt Bica; Ernst Böcskör; Lucie Brezková; Johann Dantinger; Mateusz Giszterowicz; György Heizler; et al. (Meteorologische Zeitschrift, 2017)
This paper presents the recent WWRP/WMO Forecast Demonstration Project INCA-CE (INtegrating nowCAsting for Central Europe) co-funded by the European Union. Twenty-four partners of national and regional hydro-meteorological services, national and regional crisis and disaster management centers, and authorities for road management world-wide have participated in INCA-CE for international cooperation on nowcasting development, interdisciplinary cooperation for nowcasting applications and transnational cooperation for nowcasting services. INCA-CE has implemented the nowcasting system INCA at the project partner countries, applied INCA nowcasting in civil protection, operational hydrology and road safety, and improved the INCA system based on the end user's requirements. The main difference to other similar projects is that end user's involvement and the improvements involve the whole end user value chain. The project has developed several ideas for end users on how to interpret nowcasting products (INCA-SWING) and on how to deal with the nowcasting products in their working practice (INCA-MCPEX and ISW). INCA-CE is also oriented strongly to transnational cooperation in nowcasting development and implementation, in easy access to a homogenized set of nowcasting products from those INCA providers to end users in the region, and in the transnational use of real-time products by end users in cases of high impact weather across borders.